Effect of magnesium deficiency on erythrocyte aging in rats. - Elin, R. J. (1980)
Rats placed on a magnesium-deficient diet show decreased erythrocyte magnesium concentration, shortened erythrocyte survival, and erythrocyte membrane ultrastructure defects and become progressively anemic. Whether these pathologic processes are due to abnormal erythropoiesis or occur in the peripheral circulation is unknown. In the present study, magnesium and hemoglobin concentrations, reticulocyte count, erythrocyte pyrophosphatase, and pyruvate kinase activities were determined at weekly intervals for 6 weeks in whole blood and age-dependent erythrocyte fractions isolated from inbred Fisher rats fed a diet deficient in magnesium or the same diet with added magnesium. Freeze-fracture electron microscopic examinations were performed on age-dependent erythrocyte fractions to evaluate the membrane defect. The youngest red cells from magnesium-deficient rats were similar to those of control animals with respect to erythrocyte magnesium concentrations, pyrophosphatase activities, and membrane morphology. The older erythrocyte fractions from magnesium-deficient rats showed significant decreases in magnesium concentrations, pyrophosphatase activity, and the presence of membrane abnormalities. Thus, new erythrocytes produced in magnesium-deficient rats appear to be normal but rapidly develop biochemical and morphologic abnormalities with aging in a magnesium-deficient plasma environment.